2017
DOI: 10.1016/j.cels.2017.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Design of Tunable Oscillatory Dynamics in a Synthetic NF-κB Signaling Circuit

Abstract: Although oscillatory circuits are prevalent in transcriptional regulation, it is unclear how a circuit's structure and the specific parameters that describe its components determine the shape of its oscillations. Here, we engineer a minimal, inducible human nuclear factor κB (NF-κB)-based system that is composed of NF-κB (RelA) and degradable inhibitor of NF-κB (IκBα), into the yeast, Saccharomyces cerevisiae. We define an oscillation's waveform quantitatively as a function of signal amplitude, rest time, rise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 42 publications
1
34
0
Order By: Relevance
“…To construct atg8-G116A fission yeast strain, we used overlap-extension PCR to assemble the following three fragments into one final PCR product: the C-terminal region of the atg8 ORF (amplified using the primer 5’-TTAATTAACCCGGGGATCCGctaaaaaggaaacactgttGcaaat-3’, which introduces the G116A mutation, and the primer 5’-acaacacccattgtttttgtca-3’), a kanMX marker from pFA6a plasmid (amplified using primers 5’- CGGATCCCCGGGTTAATTAA-3’ and 5’- CGATGAATTCGAGCTCGTTT-3’), and the sequence downstream of the atg8 ORF (amplified using primers 5’-AAACGAGCTCGAATTCATCGatcaacaatttgcctgttttaaga-3’ and 5’-aaggatagaatcagctgatgat-3’), and transformed the final PCR product into fission yeast. Plasmids expressing proteins in budding yeast under the control of the pTEF1 promoter were constructed using pNH605 vectors (plasmids cut with PmeI before transformation) ( Zhang et al, 2017 ). To create a fission yeast strain expressing Atg8 tagged at its N-terminus with mYFP or mEGFP, Patg8 promoter, from −609 to +3 bp with respect to the start codon of the atg8 gene, was cloned between the Bgl II and Pac I sites of pFA6a-kanMX6-P41nmt1-mYFP or pFA6a-kanMX6-P41nmt1-mEGFP plasmid to replace the P41nmt1 promoter ( Bähler et al, 1998 ).…”
Section: Methodsmentioning
confidence: 99%
“…To construct atg8-G116A fission yeast strain, we used overlap-extension PCR to assemble the following three fragments into one final PCR product: the C-terminal region of the atg8 ORF (amplified using the primer 5’-TTAATTAACCCGGGGATCCGctaaaaaggaaacactgttGcaaat-3’, which introduces the G116A mutation, and the primer 5’-acaacacccattgtttttgtca-3’), a kanMX marker from pFA6a plasmid (amplified using primers 5’- CGGATCCCCGGGTTAATTAA-3’ and 5’- CGATGAATTCGAGCTCGTTT-3’), and the sequence downstream of the atg8 ORF (amplified using primers 5’-AAACGAGCTCGAATTCATCGatcaacaatttgcctgttttaaga-3’ and 5’-aaggatagaatcagctgatgat-3’), and transformed the final PCR product into fission yeast. Plasmids expressing proteins in budding yeast under the control of the pTEF1 promoter were constructed using pNH605 vectors (plasmids cut with PmeI before transformation) ( Zhang et al, 2017 ). To create a fission yeast strain expressing Atg8 tagged at its N-terminus with mYFP or mEGFP, Patg8 promoter, from −609 to +3 bp with respect to the start codon of the atg8 gene, was cloned between the Bgl II and Pac I sites of pFA6a-kanMX6-P41nmt1-mYFP or pFA6a-kanMX6-P41nmt1-mEGFP plasmid to replace the P41nmt1 promoter ( Bähler et al, 1998 ).…”
Section: Methodsmentioning
confidence: 99%
“…Such a complexity makes it difficult to associate the specific contributions of canonical Smad signaling and non-Smad signaling with the biological functions of TGF-β signaling. Recent studies have provided a synthetic biology approach for bypassing this problem by expressing mammalian signaling circuits in yeast [104][105][106], which creates an insulated environment to avoid the complicated factors in the original mammalian cellular context. This approach provides new possibilities for mimicking orthogonal signaling cascades and understanding how perturbations change cell signaling in an insulated environment.…”
Section: Challenges and Future Outlookmentioning
confidence: 99%
“…When oscillations were first described in single cells [ 8 ], mathematical modelling also suggested that higher expression level of NF-κB could be responsible for the dampening of the oscillations [ 70 ] but this feature was not confirmed experimentally [ 71 ]. Overall, we can anticipate that even subtle variations in players of the NF-κB regulatory circuitry can lead to diverse dynamics and such diversity represents the necessary adaptive flexibility to coordinate diverse biological functions, a hypothesis that has recently started to be explored systematically using synthetic NF-κB genetic circuits [ 72 ].…”
Section: Single-cell Dynamics: Main Insights On Nf-κb Regulation Omentioning
confidence: 99%